Optimal Capacitor Placement in Unbalanced Electrical Power Distribution Systems through Differential Evolution Algorithm - De Oliveira Motta Serrano, Hugo [UNESP]; Rupolo, Diogo [UNESP]; Sanches Mantovani, José Roberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The problem of optimal capacitor placement (OCP) in three-phase and unbalanced radial distribution systems consists in determining the types, rated power, and in which phases to allocate them, taking into account the physical and operational constraints of the electrical networks, together with the energy supply quality standards required by regulatory agencies. The control scheme must also be defined, that is, the number of modules of switched capacitors that must operate at different load levels. In order to solve this problem, we propose a differential evolution (DE) metaheuristic, which provides the location and dimensions of the fixed and switched capacitors in the primary feeders of three-phase and unbalanced radial distribution systems. Tests are carried out considering the proposed methodology for an unbalanced three-phase system with 135 nodes.
Keywords: Capacitor Placement; Differential Evolution Metaheuristics; Unbalanced Three-phase Distribution Systems